Strategic Information Technology Plan: A Vital Component in the Corporate Strategy of Banks - Liang, Thow Yick (Institutional Knowledge at Singapore Management University, 1994)
The traditional areas of commercial banks, such as consumer banking, corporate banking, and treasury operations of investment banking have been computerized. Decision support systems have been used extensively in areas such as consumer account analysis, customer profitability analysis, and calculation of the cost of funds and bond yield. In addition, expert systems are gradually being used on an irregu;ar basis in banks. Despite the fairly high level of information technology (IT) utilization, the present information systems of the banks are in management and operation decisional areas, rather than in strategic applications. A proper plan for strategic utilization of IT is missing. This study explores the areas in which banks can use IT strategically to emerge as winners in the highly competitive banking industry. Several Management Information Systems frameworks, such as Porter's competitive framework is adapted to examine such strategic impact.